Welfare and employment: a European dilemma? - Werner Eichhorst; Anton Hemerijck (Institute for the Study of Labor (IZA), 2008)
The majority of the Member States of the European Union have undertaken remarkably comprehensive welfare and labor market reforms in the years since the 1990s. Many of these reforms, however, have not followed the conventional retrenchment and deregulation recipes, but rather took a liking to social pacts, activation, active ageing/avoidance of early retirement, part-time work, lifelong learning, parental leave, gender mainstreaming, flexicurity (balancing flexibility with security), reconciling work and family life. At first sight, these reforms seem to have resulted in relatively robust employment growth, especially for women and more recently older workers. European economic integration has fundamentally recast the boundaries of national systems of employment regulation and social protection, both by constraining the autonomy for domestic policy options but also by opening opportunities for EU-led social and employment coordination and agenda setting.
urn:nbn:de:101:1-20081216249
Keywords: J21; 330; Labor market reforms; European integration; welfare states; Sozialstaat; Sozialreform; Arbeitsmarktflexibilisierung; Beschäftigungspolitik; EU-Politik; Wirkungsanalyse; Beschäftigungseffekt; EU-Staaten